An opinion on the genus Fujiscon Ito, 1991 (Eutardigrada, Hypsibiidae) - Pilato, Giovanni; Binda, Maria Grazia (Zootaxa, 2003)
The structure of the claws of the genus Fujiscon and the validity of this genus are discussed. According to the authors one can conclude that the claws of Fujiscon are of Hypsibius type with an evident septum between the common basal portion and the secondary branch. But such a septum is present also in other types of claws, and, in some cases, its presence is a variable character (in some species of some genera a septum can be present and well developed, or more or less evident, or absent in different claws of the same specimen). In conclusion, Fujiscon seems to be a non-valid genus because it does not differ from Diphascon.